Analysis Of The Value Of Struggle In The Film ‘Mencuri Raden Saleh’ (Charles Sanders Peirce's Semiotics) - Tryan Nugraha; Fauzan Heru Syahputra (UNIVERSITAS PAKUAN, 2026)
The film Mencuri Raden Saleh (2022) by Angga Dwimas Sasongko combines action, drama, and moral messages that represent the values of struggle, such as courage, solidarity, and sacrifice, through its plot, conflict, and visual symbols. As a form of mass media, film plays a role in shaping collective consciousness; therefore, this study utilizes Charles Sanders Peirce's semiotics to analyze the use of icons, indices, and symbols in constructing a meaning of struggle that is both educational and reflective for the audience. This research employs a qualitative descriptive method with a sign analysis technique consisting of representamen, object, and interpretant. Data were collected through film observation, visual documentation. The research findings indicate that the values of struggle—such as courage, solidarity, sacrifice, determination, and perseverance—are strongly represented through visual, symbolic, and narrative elements in the film. Historical symbols, such as the painting